2015
DOI: 10.3390/ijms160816953
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Profiling of B Cell Subsets from Systemic Lupus Erythematosus Patients Reveals Promising Novel Biomarkers

Abstract: MicroRNAs control the differentiation and function of B cells, which are considered key elements in the pathogenesis of systemic lupus erythematosus (SLE). However, a common micro(mi)RNA signature has not emerged since published data includes patients of variable ethnic background, type of disease, and organ involvement, as well as heterogeneous cell populations. Here, we aimed at identifying a miRNA signature of purified B cells from renal and non-renal severe SLE patients of Latin American background, a popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 23 publications
0
22
0
1
Order By: Relevance
“…mir-21, mir-25 and mir-106b, which are elevated in B cells, are upregulated in T cells as well, and the positive correlation with sledai in total pBmcs should not be ascribed to B cells 27 . However, elevated mir-21 in B cells has been confirmed in further studies to be associated with disease severity 144 and lupus nephritis 145 . recently, Wu et al demonstrated elevated levels of mir-7, mir-21 and mir-22 in B cells of newly diagnosed treatment-naïve sle patients 144 .…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…mir-21, mir-25 and mir-106b, which are elevated in B cells, are upregulated in T cells as well, and the positive correlation with sledai in total pBmcs should not be ascribed to B cells 27 . However, elevated mir-21 in B cells has been confirmed in further studies to be associated with disease severity 144 and lupus nephritis 145 . recently, Wu et al demonstrated elevated levels of mir-7, mir-21 and mir-22 in B cells of newly diagnosed treatment-naïve sle patients 144 .…”
mentioning
confidence: 82%
“…3). moreover, in the lupus nephritis group compared to the sle group, mir-145 was upregulated, yet levels of mir-18b, mir-21, mir-29c, mir-345 and mir-365 were alleviated 145 .…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…These new classification criteria take into account additional forms of cutaneous lupus and newly described autoantibodies, which may provide further guidance in clinical judgment of SLE. New promising biomarkers for SLE are currently under development, including microRNA [25], presence of urinary immune cells [26], and genetic biomarkers such as specific polymorphisms of MHC, interferon responsive factors, and integrins [27]. Together with updated classification criteria and new biomarkers, we are hopeful to see an increase in certainty of diagnosis for variable presentations of SLE.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the certain role of polymorphisms in treatment response, recently the involvement of epigenetic mechanisms in personalized medicine has been catching on. This theme is faced by Cacabelos and Duroux-Richard and their respective collaborators [ 11 , 14 ]. Cacabelos, in particular, presented the epigenetics mechanisms in the Alzheimer disease (AD) and aging dealing with the three major regulatory elements—DNA methylation, histone modifications and miRNA regulation—responsible for the control of metabolic pathways at the molecular level [ 11 ].…”
mentioning
confidence: 99%